ENGLISH INJECTION FOR THALASSEMIA: PELATIHAN BAHASA INGGRIS BAGI PENYANDANG THALASSEMIA BANYUMAS DI UNIVERSITAS NAHDLATUL ULAMA PURWOKERTO - Dinar Faiza; Ade Christanty Yudha Bestari; Meilina Haris Mayekti (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Thalassemia is a hereditary disease caused by abnormalities in red blood cells in which the individual has a gene disorder that causes reduced production of hemoglobin in red blood cells. People with Thalassemia, especially the type of Thalassemia Major, need routine therapy and medication. These routine therapy and medication activities sometimes cause various problems and obstacles in the lives of people with thalassemia both physically and psychologically. Individuals with thalassemia also show impaired psychosocial and school functioning. The desire and enthusiasm for learning decreased, giving rise to human resources with low educational backgrounds. The lack of education especially the knowledge of health terms in English is one of the problems. The program of English Injection for Thalassemia intended to create an English learning space for people with Thalassemia. English Injection for Thalassemia aimed to provide English education, especially information about medical terms which are important in the treatment of thalassemia. The object of the program is the members of the Association of Indonesian Thalassemia Patients, commonly called PPTI Banyumas. The method of implementing this program was used fun learning methods and media. It provided English training in groups through indoor and outdoor activities with basic English expressions and English medical terms for Thalassemia